Possibilities of Using Social Internet Research in Constructing Educational Knowledge - Kubinowski, Dariusz (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
As a result of radical social and cultural transformations with the key role of new media technologies, epistemologies, methodologies and methods of social research have been changed around the academic world. In this worldwide process one of the emergent family of methods is social Internet research. The main aim of this article is to identify and characterise the nature, key features, and three general genres of social Internet research. The author presents this elaboration with special intention of stimulating application of Internet research on the field of constructing new educational knowledge as an important need of educational sciences in current Poland. Additionally, we can find in the text the author’s interpretation of virtuality understood as a methodological category, and a description of hypermedia research report understood as a new format of scientific elaboration.